STRATEGI PENGEMBANGAN KELEMBAGAAN KOPERASI PERTANIAN BERBASIS JAGUNG DI PROVINSI GORONTALO - Baga, Lukman M (Jurnal Manajemen Pembangunan Daerah, 2009)
success of an integrate agribusiness system of a commodity must be followed by the increase of farmers’ bargain position, especially the small scale agribusiness runs by farmers. Otherwise, farmer will continue to be marginalized, and sustainable production is hard to be achieved. Farmer organization in Indonesia is relatively has weak position and cannot improve farmers’ bargain position since it is still in social institution form (i.e. farmer group), and yet become a socio-economic institution (cooperative). In many countries, farmers’ cooperative not only improves the production, productivity and product quality, but also lead to increase in welfare and life quality of its members. This study specifically aimed to develop corn farmer co-operative in Gorontalo Province. SWOT analysis was being used to formulate the strategy, followed by strategy mapping in road-map as guidance for local government to develop corn farmer co-operative that suitable with its character.Keyword: agribusiness, corn, farmer group, farmer co-operative, Gorontalo.